Collaboration and Communication. Issue 175 (20th February 2018) - Balser, Tina J.; Grabau, Ashli A.; Kniess, Dena; Page, Laura A.
Abstract: This chapter discusses how collaboration and communication impacts the assessment process to ensure success.